Efektifitas Pemanfaatan Kemampuan Guru Ekonomi Kota Surabaya dalam Menulis Proposal Penelitian Tindakan Kelas - Soesatyo, Yoyok; Soejoto, Ady; Suratman, Bambang; Subroto, Waspodo Tjipto; Harti, Harti; Hakim, Luqman (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2018)
Training Objectives in Community Service is to (1) provide teachers understanding about TOD; (2) provide mentoring of Classroom Action Research proposal formulation; (3) provide teacher assistance on study of Classroom Action Research proposal made by teacher. Subject in this Community Service is SMP teacher who are incorporated in the Economic Teacher in Surabaya. The object of this Community Service is training preparation of Classroom Action Research proposal. Community Service implementation method is broadly divided into 2 activities, namely training of Classroom Action Research proposal preparation with varied lecture method and Practice preparation of Classroom Action Research proposal with simulation and presentation method. The results obtained in Community Service are quite effective (1) participants have enthusiasm in listening to material explanation as much as 92%; (2) Participants who attended Classroom Action Research Proposal Writing Training from start to end of training as much as 98%; (3) Participants who are able to Practice Classroom Action Research Proposal Writing in accordance with the available time of 85%; (4) Participants who have interest in doing Classroom Action Research when in school as much as 100%.